Transformational Leadership, Market-Oriented Culture, and Implementation of Total Quality Management Practices: Proposed Conceptual Model - Desalegn Urgessa Yadeta; Matiwos Ensermu Jaleta; Mesfin Workineh Melese (European Scientific Journal, ESJ, 2022)
The focus of this study was to consolidate the existing knowledge on leadership, market-oriented culture, and TQM by proposing a conceptual model providing a starting point for researchers and practitioners seeking to implement market-oriented culture and TQM in organizations and offering suggestions for future research. A systematic literature review was undertaken to review works published on transformational leadership, market-oriented culture, and TQM practices. The review's key findings show that transformational leadership is required for successful TQM implementation and market-oriented culture in organizations and is critical to sustaining their improvement. This research is based on a systematic literature review of works published on transformational leadership, market-oriented culture, and TQM practices. Transformational leadership is critical for both market-oriented culture and TQM implementation success. There is a need to develop a new model of transformational leadership that encompasses the leadership behavior needed for both market-oriented culture and TQM.